Microclimate in forests with varying leaf area index and soil moisture: potential implications for seedling establishment in a changing climate - von Arx, Georg; Pannatier, Elisabeth Graf; Thimonier, Anne; Rebetez, Martine (My University, 2013)
1. Forest microclimate is crucial for the growth and survival of tree seedlings and understorey vegetation. This high ecological relevance contrasts with the poor functional and quantitative understanding of how the properties of forest ecosystems influence forest microclimate. 2. In a long-term (1998-2011) trial, we investigated how temporal patterns of microclimate below sparse and dense forest canopy related to those of nearby open areas and how this relationship was influenced by soil moisture and seasonality. Air temperature (T), vapour pressure deficit (VPD), soil matrix potential and leaf area index (LAI) were measured in a unique set-up of below-canopy and open-area meteorological stations at eleven distinct forest ecosystems, characteristic of subalpine and temperate climate zones. Data from these plots were analysed for the moderating capacity of the canopy, that is, the differences between below-canopy and open-area microclimate, with respect to (i) long-term means, (ii) dynamics within homogeneous moist- vs. dry-soil periods and (iii) diurnal patterns. 3. The long-term mean moderating capacity of the canopy was up to 3.3 degrees C for daily T-max and 0.52kPa for daily VPDmax, of which soil moisture status alone accounted for up to 1.2 degrees C (T-max) and 0.21kPa (VPDmax). Below dense canopy (LAI>4), the moderating capacity was generally higher when soils were dry and increased during dry-soil periods, particularly in spring and somewhat less in summer. The opposite pattern was found below sparse canopy (LAI<4). At the diurnal level, moderating capacity below dense canopy was strongest in mid-afternoon and during dry-soil conditions, whereas peak moderation below sparse canopy occurred in mid-morning and during moist-soil conditions. 4. Synthesis. Our results suggest a threshold canopy density, which is probably linked to site-specific water availability, below which the moderating capacity of forest ecosystems switches from supportive to unsupportive for seedling establishment. Under supportive moderating capacity, we understand a stronger mitigation during physiologically most demanding conditions for plant growth. Such a threshold canopy density sheds new light on forest resilience to climate change. Climate change may alter forest canopy density in a way that precludes successful establishment of tree species and ultimately changes forest ecosystem structure and functioning.